Frequency Stability For Two Generators Using Robust Control (HâˆžController) - Nour, Agab Bakheet Mohammed; Rameli, Mochammad; Effendi, Rusdhianto (JAVA Journal of Electrical and Electronics Engineering, 2014)
The purpose of this paper is to design a robust control using H ? controller theory to obtain a frequency stability of two different synchronous generator engines. Where the condition of power change from nominal conditions 96.81KVA to a minimum value 60.5KVA or maximum value120.03KVA. Besides, it is used a PID controller as a Coordinator in collaboration with H ? controller to obtain the minimum phase angle between the two generators. Based on the analysis show good results where the output voltage lost from the system is minimal.